الضوابط الفنية في مخطوطات المكتبة الجمنية - رتيمي, محمد علي (ملتقى سيدي موسى للتراث الجبلي, 2017)
Keywords: Manuscrits

‘How were the traces of their edifices erased?’ Archaeological / ethno-historical survey of Jerba, Tunisia - Holod, Renata (Khalili Research Centre Seminars, 2017)
Keywords: Archéologie -- Djerba

الحبيب بكار - الجريري, لطفي (ملتقى الجيلاني بن الحاج يحيى لأعلام جربة (الدورة الثانية), 2017)
Keywords: Biographies -- Djerba -- 20e siècle

البشير قوشة - قوشة, محرز (ملتقى الجيلاني بن الحاج يحيى لأعلام جربة (الدورة الثانية), 2017)
Keywords: Biographies -- Djerba

حمادي اللواتي - اللواتي, مهدي (ملتقى الجيلاني بن الحاج يحيى لأعلام جربة (الدورة الثانية), 2017)
Keywords: Biographies -- Djerba -- 20e siècle

دور الجيلاني بن الحاج يحيى في المعجمية - بن مراد, إبراهيم; إبراهيم, عبد الواحد (ملتقى الجيلاني بن الحاج يحيى لأعلام جربة (الدورة الثانية), 2017)

الصادق بن مرزوق - الجريري, لطفي (ملتقى الجيلاني بن الحاج يحيى لأعلام جربة (الدورة الثانية), 2017)
Keywords: Biographies

Djerba aux yeux des photographes : Un voyage dans le temps et dans l'espace - Ben Salah, Imed (Voyages et voyageurs aux temps des Lumières (Djerba), 2017)

الفكر الموسيقي المقامي العربي، المقومات الحضاريّة - قوجة, محمد (المقامية من منظور الحداثة, 2017)

Le commerce transsaharien à la lumière de l’ibadisme maghrébin : cultures économiques, marchés et réseaux médiévaux - Aillet, Cyrille (Séminaire pluridisplinaire d’histoire économique HISOMA, CIHAM et LARHRA, 2017)
L’historiographie a maintes fois souligné le rôle pionnier des populations berbères affiliées à la doctrine dissidente de l’ibadisme dans le développement du commerce transsaharien, en particulier la traite des esclaves. Cette branche de l’islam serait en effet une parfaite illustration de « l’ascétisme intramondain » mis en avant par Max Weber dans son analyse des relations entre religion et économie. Nous reviendrons ici sur la place de cette minorité dans l’évolution des économies sahélo-méditerranéennes, sur ses modes d’interaction sociale, sur ses pratiques et représentations économiques
Keywords: Commerce transsaharien

المخطوط بين التحقيق والدراسة - البوجديدي, علي (المخطوط بين التحقيق و الدراسة, 2017)
Keywords: Manuscrits -- Djerba

Les défis de la gestion et de la conservation des sites du patrimoine mondial au Maghreb: présentation sur la vallée du M’zab (Algérie) - Babanedjar, Younes (Atelier régional sur le processus de proposition d’inscription de sites culturels sur la Liste du patrimoine mondial, 2017)
Keywords: Monuments -- conservation -- Mzab

Le rôle de la société civile et de la population locale dans l’inscription, la gestion et la sauvegarde des biens du patrimoine mondial - Ben Yahyaten, Sassi; Kabla, Annie; Camellieri, Jacqueline; Baiouli, Mohamed; Hajji, Ahlam (Atelier régional sur le processus de proposition d’inscription de sites culturels sur la Liste du patrimoine mondial, 2017)
Keywords: Monuments -- conservation -- Djerba

Présentation du patrimoine culturel et naturel de l’île de Djerba - Bourgou, Mongi; Bouabid, Naceur (Atelier régional sur le processus de proposition d’inscription de sites culturels sur la Liste du patrimoine mondial, 2017)
Présentation générale de l’île de Djerba (Histoire, développement de l’île, patrimoine culturel et naturel) Les défis et les enjeux pour Djerba (conséquences du développement urbain, effets indésirables du tourisme et pressions environnementales, protection du patrimoine)
Keywords: Monuments -- conservation -- Djerba

Etat de conservation du bien et facteurs affectant le bien: protection légale existante et à mettre en place - Rihane, Mourad; Revault, Philippe; Abdelkafi, Jellal; Ben Azaiez, Maroua; Fraoua, Ridha; Daghfass, Houcine; Dermech, Ltaif (Atelier régional sur le processus de proposition d’inscription de sites culturels sur la Liste du patrimoine mondial, 2017)
Cadre administratif et réglementation en Tunisie pour la gestion et la sauvegarde des sites du patrimoine mondial ; faisabilité d’une approche territoriale pour la protection et la conservation des composantes du site de l’île de Djerba
Keywords: Monuments -- conservation -- Djerba

تأملات بقدية في عقود الحارثي الفضية - الباروني, سناء مهني (الشيخ سالم بن حمد بن سليمان الحارثي حياته وفكره, 2017)

عنابة الشيخ بجمع المخطوطات والوثائق وتأسيس مكتبته - الباروني, يعقوب بن سعيد (الشيخ سالم بن حمد بن سليمان الحارثي حياته وفكره, 2017)

قراءة في حياة الشيخ الحارثي ومكونات شخصيته ومعالمها - البوسعيدي, سالم بن سعيد (الشيخ سالم بن حمد بن سليمان الحارثي حياته وفكره, 2017)

الشيخ سالم بن حمد الحارثي كما عرفته - الجعبيري, فرحات بن علي (الشيخ سالم بن حمد بن سليمان الحارثي حياته وفكره, 2017)

دور الشيخ الحارثي في الإصلاح الإجتماعي - الحارثي, راشد بن علي (الشيخ سالم بن حمد بن سليمان الحارثي حياته وفكره, 2017)
Keywords: Réformisme -- Oman

ذكرى نبوة لأبوة - الحارثي, عبد الله بن سالم (الشيخ سالم بن حمد بن سليمان الحارثي حياته وفكره, 2017)

نشأته وحياته وعلافته بعلماء عصره - الراشدي, أحمد بن ناصر (الشيخ سالم بن حمد بن سليمان الحارثي حياته وفكره, 2017)

المنهج التربوي لدى الشيخ الحارثي - الراشدي, سعيد بن مسلم (الشيخ سالم بن حمد بن سليمان الحارثي حياته وفكره, 2017)

فراءة في بعض مراسلات الشيخ الحارثي - الراشدي, مبارك بن عبدالله بن خالد (الشيخ سالم بن حمد بن سليمان الحارثي حياته وفكره, 2017)

الشيخ الحارثي قاضيا - الريامي, حسن بن خلف (الشيخ سالم بن حمد بن سليمان الحارثي حياته وفكره, 2017)

تعليقات الشيخ الحارثي على كتاب العقد الثمين - السيابي, عبد الله بن راشد (الشيخ سالم بن حمد بن سليمان الحارثي حياته وفكره, 2017)

ما نزل في القرآن مطابقا للغة أهل عمان من خلال كتاب العقود الفضية - الصوافي, سعيد بن راشد (الشيخ سالم بن حمد بن سليمان الحارثي حياته وفكره, 2017)

الشيخ الحارثي عالما وفقيها - العبري, زاهر بن عبد الله (الشيخ سالم بن حمد بن سليمان الحارثي حياته وفكره, 2017)

التواصل العلمي بين الشيخين إبراهيم بن سعيد العبري وسالم بن حمد الحارثي - العبري, علي بن هلال (الشيخ سالم بن حمد بن سليمان الحارثي حياته وفكره, 2017)

الحس الوطني في ديوان الشيخ الحارثي - المعمري, يوسف بن سليمان (الشيخ سالم بن حمد بن سليمان الحارثي حياته وفكره, 2017)

القضايا العقدية في فكر الشيخ الحارثي - المنصوري, مبروك (الشيخ سالم بن حمد بن سليمان الحارثي حياته وفكره, 2017)

منهجية الشيخ الحارثي التاريخية في كتاب العقود الفضية - الهاشمي, سعيد بن محمد (الشيخ سالم بن حمد بن سليمان الحارثي حياته وفكره, 2017)

الشيخ الحارثي فقيها - باجو, مصطفى بن صالح (الشيخ سالم بن حمد بن سليمان الحارثي حياته وفكره, 2017)

الحس الوجداني في شعر الشيخ الحارثي - بوحجام, محمد بن قاسم ناصر (الشيخ سالم بن حمد بن سليمان الحارثي حياته وفكره, 2017)
Keywords: Poésie -- Oman

القاضي العادل عند الإباضية، الشيخ الحارثي أنموذجا - حاج إبراهيم, عبد الرحمان (الشيخ سالم بن حمد بن سليمان الحارثي حياته وفكره, 2017)
Keywords: Justice -- Oman

قراءة في منهجية الشيخ الحارثي من خلال كتابه المسالك النقية - عليان, رأفت سيد حسين (الشيخ سالم بن حمد بن سليمان الحارثي حياته وفكره, 2017)

منهج تحقيق السنة عند الشيخ الحارثي من خلال مؤلفاته - كروم, أحمد بن حمو (الشيخ سالم بن حمد بن سليمان الحارثي حياته وفكره, 2017)

مكتبة الشيخ الحارثي - كرير, خديجة (الشيخ سالم بن حمد بن سليمان الحارثي حياته وفكره, 2017)
Keywords: Bibliothèques -- Oman

الآثار الاجتماعية لعملية التحضر بالمجتمع العماني: دراسة مطبقة على واليتي السيب وقريات بمحافظة مسقط - الغافرية, جليلة بنت رشد; أمبوسعيدية, زيانة بنت عبد الله; العلوية, ضحة بنت سالم (الهيمنة الحضرية والنسيج العمراني التقليدي في سلطنة عمان, 2017)
Keywords: Urbanisme -- Oman

ثقافة التراث العمراني: التجربة الجزائرية- مدينة غرداية - روباش, جميلة (الهيمنة الحضرية والنسيج العمراني التقليدي في سلطنة عمان, 2017)
Keywords: Monuments -- Mzab

أثر السياحة التراثية في صون المنازل التقليدية والمعالم الأثرية في منطقة بات، سلطنة عمان - الشقصي, سامية سليم (الهيمنة الحضرية والنسيج العمراني التقليدي في سلطنة عمان, 2017)
Keywords: Tourisme -- Oman

اتجاهات تحقيق التوافق بين الصالة والمعاصرة فى العمارة العمانية - عبد الهادى, محمد ابراهيم محمد (الهيمنة الحضرية والنسيج العمراني التقليدي في سلطنة عمان, 2017)
Keywords: Urbanisme -- Oman

الصناعات التقليدية التراثية بالنسيج العمراني بسلطنة عمان: رؤية جغرافية للعالقات المكانية - عبد العال, سيد رمضان سيد (الهيمنة الحضرية والنسيج العمراني التقليدي في سلطنة عمان, 2017)
Keywords: Artisanat -- Oman

قياس مستوى الرضا عن التشريعات والقوانين المنظمة للنسيج العمراني الحضري في سلطنة عمان: المهندسين والمقاولين نموذجا - الفرعي, فيصل; الصبحى, نورة; الكيومي, وضحاء (الهيمنة الحضرية والنسيج العمراني التقليدي في سلطنة عمان, 2017)
Keywords: Urbanisme -- Oman

اهتمام الأفراد والمؤسسات بتأهيل البيوت الأثرية في سلطنة عمان - الحوسني, صفية بنت سلطان (الهيمنة الحضرية والنسيج العمراني التقليدي في سلطنة عمان, 2017)
Keywords: Monuments -- Oman

آراء الشباب العماني حول الهيمنة الحضرية وأثرها على الهوية المعمارية في سلطنة عمان - الربعاني, أحمد بن حمد; السالمي, حمد بن سليمان; العزري, أمل بنت سليمان; الدايري, هدى بنت مبارك; الحضرمي, شرى بنت سيف; بني عرابة, أسماء بنت مبارك; العامري, انتصار بنت حمد; أمبوسعيدي, دى بنت علي; الشماخي, زكية بنت سالم (الهيمنة الحضرية والنسيج العمراني التقليدي في سلطنة عمان, 2017)
Keywords: Urbanisme -- Oman

landscape Linguistic: Muscat of fabric urban the in businesses retail Small - Tuzlukova, Victoria; Eltayeb, Christine (الهيمنة الحضرية والنسيج العمراني التقليدي في سلطنة عمان, 2017)
Keywords: Urbanisme -- Oman

واقع الاهتمام بتعزيز الهوية المعمارية لدى طلبة التعليم الأساسي وما بعد الأساسي بسلطنة عمان من وجهة نظر المعلمين - الربعاني, أحمد بن حمد; العزري, أمل بنت سليمان; الدايري, هدى بنت مبارك; الحضرمي, بشرى بنت سيف; بني عرابة, أسماء بنت مبارك; العامري, انتصار بنت حمد; أمبوسعيدي, ندى بنت علي; الشماخي, زكية بنت سالم (الهيمنة الحضرية والنسيج العمراني التقليدي في سلطنة عمان, 2017)
Keywords: Enseignement -- Oman

Settlement Mirbat of Study Case Oman in Tourism Sustainable Embracing - Hashim, Aliya al- (الهيمنة الحضرية والنسيج العمراني التقليدي في سلطنة عمان, 2017)
Keywords: Tourisme -- Oman

التنمية المكانية للمستوطنات العمرانية في أرخبيل سقطرى (مدينة حديبو : دراسة تطبيقية) - المحمدي, عمر بن سالم (الهيمنة الحضرية والنسيج العمراني التقليدي في سلطنة عمان, 2017)
Keywords: Urbanisme -- Zanzibar

Mutrah of spaces open traditional on primacy urban of impact The - Aljabri, Hanan (الهيمنة الحضرية والنسيج العمراني التقليدي في سلطنة عمان, 2017)
Keywords: Urbanisme -- Oman

استدامة التنمية الحضرية للمدن - تجربة مدينة استوكهولم - حمدناالله, طارق حمد ناالله احمد (الهيمنة الحضرية والنسيج العمراني التقليدي في سلطنة عمان, 2017)
Keywords: Fiqh -- Urbanisme

La restitution des savoir-faire traditionnels et sa contribution dans la conservation du patrimoine ; cas d’étude : la vallée du Mzab (Algérie) - Kechacha-Berdi, Imane (Conservation et valorisation du patrimoine architectural et paysager des sites côtiers méditerranéens, 2017)
Keywords: Architecture -- Mzab

Patrimoine vernaculaire méditerranéen : L’architecture de l’ile de Djerba et ses limites d’adaptation au mode de vie de l’insulaire Djerbien d’aujourd’hui - Ben Younes, Houda (Conservation et valorisation du patrimoine architectural et paysager des sites côtiers méditerranéens, 2017)
Keywords: Architecture -- Djerba

The Ibāḍiyya in the Context of Early Islamic Theology and Law - Pökel, Hans-Peter (The Ibāḍiyya in the Context of Early Islamic Theology and Law, 2017)
Keywords: Fiqh

Early Ibāḍī Law and its Ḥanafī Background - Jokish, Benjamin (The Ibāḍiyya in the Context of Early Islamic Theology and Law, 2017)
Keywords: Fiqh

The Early Development of Ibāḍī Law in Oman - Kondo, Yohei (The Ibāḍiyya in the Context of Early Islamic Theology and Law, 2017)
Keywords: Fiqh

Some Remarks on Theological and Juridical Problems Regarding the Early Ibāḍiyya According to the Kitāb al-Taḥrīsh - Sayyid, Ridwan al- (The Ibāḍiyya in the Context of Early Islamic Theology and Law, 2017)
Keywords: Fiqh

Ḍirār b. ʿAmr’s Kitāb al-Taḥrīsh (Second Century H.) and its Importance for the History of Early Iraqi Ibāḍism - Ess, Josef van (The Ibāḍiyya in the Context of Early Islamic Theology and Law, 2017)
Keywords: Fiqh; Foi -- Traité -- 9e siècle; Ġaṭāfānī, Ḍirār b. ʿAmr al-

The Influence of Ibāḍī siyar on the Orientalists’ Understanding of the Formation of Islam - Salimi, Abdulrahman al- (The Ibāḍiyya in the Context of Early Islamic Theology and Law, 2017)
Keywords: Orientalisme -- Ibadisme

Cheikh Muhammad Attfayech et la reconfiguration du champ religieux ibadite en Algérie (1870s-1914) - Jomier, Augustin (Éruditions musulmanes et colonialisme en Afrique Perspectives transsahariennes (1850-1950), 2017)
Keywords: Vie religieuse -- Mzab

Les femmes berbères dans les sources ibadites du Maghreb médiéval - Prevost, Virginie (Written sources about Africa and their study, 2017)
Keywords: Prosopographie -- Afrique du Nord

On the Significance of the Aqwal Qatada for Early Islamic Legal Thought - Salimi, Abdulrahman al- (Middle East Studies Association, 2017)
The Aqw?l Qat?da (the Sayings/teachings of Qat?da) is a collection of writings on fiqh (jurisprudence) and ?ad?th (traditions) narrated by Qat?da b. Di'ama al-Sadusi (c.60-117/680-735) that has frequently attracted the interest of present-day scholars. In addition to these writings, the discovery of a number of previously unknown texts on Ib??? jurisprudence and early legal opinions in the Maghrib region by a non-Ib??? scholar from Ba?ra now raises important questions about early Ib??? history and the proper methods of recording information during Islam’s formative period during the first half of the 2nd /8th century. Although these texts have not yet been published, they are the subject of intense debate amongst modern scholars. Although the Aqw?l Qat?da was never incorporated into the legal literature of the Ib??iyyah in Oman, manuscripts of the Aqw?l Qat?da have repeatedly attracted particular interest among modern scholars as it raises questions concerning the early development of the Ib??? Ba?ran community. It is a unique document because it attests to the existence of a scholarly link between Sunn?s and Ib???s during the early development of Islamic law. The fact that the legal responses and traditions of Qat?da are part of an Ib??? collection, in which the traditions of J?bir bin Zayd (one of the founders of Ibadism) have been transmitted through ‘Amr b. Harim and ‘Amr b. D?n?r, proves that Ib??? lawyers of the first generations considered Qat?da to be a faithful upholder of J?bir's doctrine. This present study on the text is based on two recently discovered manuscripts. One of these is in the D?r al-Kutub al-Mi?riyyah in Cairo, while the other is in the al-B?r?niyyah Library (al-Khiz?nah al-B?r?niyyha) on the Tunisian island of Djerba. We shall look at both of them in detail. The texts display three important features, which will be the subject of analysis: 1) fiqh opinions commonly held during the early Islamic period in Ba?ra; 2) early approaches to the collection of Islamic religious traditions including ?ad?th of the Prophet and legal opinions of the early community 3) the development of Islamic jurisprudence during the first two centuries of the Islamic era.
Keywords: Fiqh

A Compendium of Theological “Firsts:” the Significance of Early Ibadi Kalam Texts for Islamic Thought - Adem, Rodrigo (Middle East Studies Association, 2017)
This paper discusses the broader historiographical significance of recently published Ibadi texts dated to the 8th century CE. The valuable nature of these works can be demonstrated in their documentation of paradigmatic precepts and conceptual models of philosophical theology or kalam which subsequently went on to have broader influence in Islamic doctrine, exegesis, and law as a whole. Such examples indicate the methodological incumbency of incorporating Ibadi thought for the sake of properly historicizing “reason and revelation” as a category of analysis for Islamic thought. The very bifurcation of reason and revelation as distinct epistemic resources for Islamic theology finds its earliest documentation in the particular text which receives the most attention in this paper: the Radd ‘ala Ibn ‘Umayr by Abd Allah b. Yazid al-Fazari. The juxtaposition of these two resources, their role in the proof of the existence of God and prophethood, and the epistemic role and limits of human thought in determining moral value or religious injunction (which defined more commonly known debates between Mu’tazilites, Ash’aris, and other schools of thought), can all be discerned here in embryo, and likewise accompanied by surprisingly developed argumentation pointing to even earlier developmental stages. This paper offers an exposition of the abovementioned material in conversation with recent discussions by Wilferd Madelung along with a genealogy of its subsequent reception history in later traditions. This will be accompanied by historiographical reflections on the necessity of acknowledgement of these sources beyond specialists in Ibadism to include specialists in Islamic Thought as a whole.
Keywords: Fazārī, ʿAbd Allāh ibn Yazīd al-; Foi -- Traité -- 8e siècle

Ibadism and the Construction of Ethnicity in Medieval North Africa - Aillet, Cyrille (Middle East Studies Association, 2017)
While Kharijism supported the claims of the Yaman? tribes and the Persians in the East, in North Africa Ibadism was soon identified with the Berbers and contributed to shape their ethnic identity. Far from being natural, the Arab-Berber dichotomy was first constructed against the Empire, for legitimizing the new indigenous Islamic polities, in particular the Imamate of Tahart (777-909). Instead of focusing on Berber rebellion as a response to Arabic ‘oppressiveness’ or a struggle for ‘freedom’, our contribution examines how the political confrontation between the Empire and his Western confines determined the Sunni narrative on the Islamic conquest of North Africa and its local population. The polemical image of the Berbers as a wild and rebellious nation, superficially converted to Islam, was probably an answer to the Khariji threat. This is made even clearer by the existence of an Ibadi counter-discourse, preserved by Ibn Sallam al-Law?t? (end of the 9th c.) and later sources, in which the Berbers become a new chosen people and their primitiveness a sign of their religious sincerity. These surviving fa??’il al-Barbar rely on hadiths which prove to be exactly the opposite of the available Abbasid and later Sunni material. The ethnic controversy, called shu??biyya, played a political role and was not reduced to a mere literary game in this context. The Iraqi geographer al-Ya?qub?, who visited North Africa roughly at the same time when Ibn Sall?m compiled his information, observed that local Berber communities had also adopted Eastern genealogies, like the well known affiliation to Barr b. Qays. The praise of indigeneity was therefore combined with the use of other widely diffused references. Among them, the Persian shu??biyya entered North Africa and probably inspired the ‘praise of the Berbers’. The Rustamids, whose name seems to remind of a famous Iranian hero, claimed to be ‘Persians’. At the end of the 11th century, Ab? Zakariyy?’ al-W?rjl?n?, clearly associated the fa??’il al-Barbar with the fa??’il al-Furs tradition by presenting the imams as the heirs of the Sassanid kings. The legendary figure of ?Abd al-Ra?m?n b. Rustam, who rooted a Persian dynasty in a Berber land, was at the crossroad of these two intertwined legitimacies and personified the alliance of the two Gentile nations of Islam oppressed by the ‘Arabs’.

Medieval Ibadi Images of Murji'ism - Gaiser, Adam R. (Middle East Studies Association, 2017)
Early Ibadi engagements with the Murji'a reflect a profound awareness, and probably actual encounters with, Murji'a in the early Islamic world. This paper investigates the image of Murji'ism that appears in later, 6th/12th century Ibadi writings, a time when Murji'ism had ceased to exist and its main ideas had filtered into the Sunni consensus. This paper will show that later Ibadi authors, just as their Sunni counterparts, struggled to present Murji'ism as a separate firqa. Moreover, medieval Ibadi writings on the Murji'a betray a deep awareness of contemporary Sunni heresiography on the Murji'a
Keywords: Murji'isme

Ibadi Discussions on the Divine Attributes - Hoffman, Valerie J. (Middle East Studies Association, 2017)
Ibadi works have generally been overlooked in scholarship on the development of Islamic theology (kalam). From at least the early 8th century, kalam has revolved around questions about the divine attributes and their relation to God’s unity. The distinction between the attributes of God’s essence and the attributes of His acts has usually been attributed to the Mu‘tazil? theologians Ab? ’l-Hudhayl (ca. 135/752–ca. 227/842) and al-Na???m (d. between 220/835-230/845), but a recently published text written by Ib??? theologian ‘Abd All?h b. Yaz?d al-Faz?r? soon after the death of Ib??? imam Ab? ‘Ubayda Muslim b. Ab? Kar?ma (d. between 150/767-158/775) employs these terms. This is just one indication of how Ib??? texts can offer new perspectives on the development of Islamic theology. Al-Faz?r? was fully engaged in the theological controversies of Basra and Baghdad until H?r?n al-Rash?d’s persecution of the mutakallim?n in 179/795. He wrote works refuting the ideas of other theological schools, and his ideas were followed and developed among the Maghrib? Ibadis. In Oman, early resistance to kal?m was overcome in the writings of Abu ’l-Mundhir Bash?r b. Muhammad b. Ma?b?b (d. ca. 290/908). Ib??? theology on the attributes and essence of God has generally been similar to that of the Mu‘tazila, although Omani Ib???s only came to accept the doctrine of the creation of the Qur’an in the late 19th century. This paper examines Ibadi writings on the divine attributes from the earliest available texts to the twentieth century. Ibadi responses to questions that arose concerning the divine attributes will be compared geographically and chronologically with each other and with the articulations of other schools. In modern Sunni thought, these questions are generally ignored or even deemed irrelevant, but they remained vital much longer to Ibadi scholars, for whom they were central to the definition of the faith. The theological intricacies surrounding these questions received less attention over the course of the twentieth century, but Abdul Aziz bin Baz’s public denunciation of the Ibadis as infidels for their rejection of the eternity of the Qur’an and of the possibility of seeing God led the Mufti of Oman to provide a public—and hence simplified—explanation of Ibadi teachings on these issues. Nonetheless, Omani policy under Sultan Qaboos (r. 1970-present) and current Ibadi attitudes have emphasized pan-Islamic unity, at the expense of specifically Ibadi doctrinal articulations.

L’expérience archivistique du Centre Culturel Méditerranéen à Houmt Souk, Djerba - Teghlet, Zouhair (Arts et musiques tunisiens, dimensions arabo-musulmanes africaines et méditerranéennes : l’empreinte maghrébine, 2017)
Keywords: Vie culturelle -- Djerba

The College of Islamic Law in Oman - Mawali, Ziyad Al- (Summer School on Ibadism: “Understanding Diversity Within Islam”, 2017)

Ibadi Doctrine in Contemporary Djerba - Ben Yahiaten, Gacem (Summer School on Ibadism: “Understanding Diversity Within Islam”, 2017)

Mystical Traditions in Islam - Makris, Gerassimos (Summer School on Ibadism: “Understanding Diversity Within Islam”, 2017)

The Question of Umma and Religious Sectarianism in Islam - Ioannidou, Ioanna (Summer School on Ibadism: “Understanding Diversity Within Islam”, 2017)

The Ibadi Imamate Tradition - Jovanovic, Marco (Summer School on Ibadism: “Understanding Diversity Within Islam”, 2017)

Education in Oman - Wolfram, Reiss (Summer School on Ibadism: “Understanding Diversity Within Islam”, 2017)

Ibadism. Theology, Pluralism, Understanding - Ziaka, Angeliki (Summer School on Ibadism: “Understanding Diversity Within Islam”, 2017)

Contesting Spaces: Ibadis in M’zab from an anthropological perspective - Boufrikha, Oussama (Summer School on Ibadism: “Understanding Diversity Within Islam”, 2017)

Berber Ibadi nationalism in the Colonial North Africa - Bartoli, Luca (Summer School on Ibadism: “Understanding Diversity Within Islam”, 2017)
Keywords: Berbérisme -- Afrique du Nord

Maghrebian Ibadism in the Middle Ages - Bahmani, Salah (Summer School on Ibadism: “Understanding Diversity Within Islam”, 2017)
Keywords: Ibadisme -- Afrique du Nord

Berber Ibadism in North Africa. From political legitimacy to a specific identity - Di Tolla, Anna Maria (Summer School on Ibadism: “Understanding Diversity Within Islam”, 2017)
Keywords: Berbérisme -- Afrique du Nord

An overview on the Berber Oasis of Siwa (Egypt) - Schiattarella, Valentina (Summer School on Ibadism: “Understanding Diversity Within Islam”, 2017)
Keywords: Linguistique -- Siwa

An Analysis of the Oriental Berber Dialects in Libya - Grimaldi, Bianca Elena (Summer School on Ibadism: “Understanding Diversity Within Islam”, 2017)
Keywords: Linguistique

Rethinking Ibadi Spaces – Geographical Portrayals of Ibadi Authority in 8th-century North Africa - Bosanquet, Antonia (Panel 65 reconsidering Kharijism in early Islamic history, 2017)

A Reappraisal of Ibāḍī Ḥadīth in Light of Ḍirār ibn ʿAmr’s Kitāb al-Taḥrīsh - Miah, Azaher (Panel 65 reconsidering Kharijism in early Islamic history, 2017)
Keywords: Hadith

Kharijism in Kufa: Accounts on Abū Bakr and ʿAlī according to Ḍirār b. ʿAmr’s (d. ca. 200/815) Kitāb al-Taḥrīsh - Akpinar, Mehmetcan (Panel 65 reconsidering Kharijism in early Islamic history, 2017)
Keywords: Foi -- Traité -- 9e siècle; Ġaṭāfānī, Ḍirār b. ʿAmr al-

The Piety and Theology of al-Ḥasan al-Baṣrī and the Question of Khārijī Influence - Goyal, Raashid S. (Panel 65 reconsidering Kharijism in early Islamic history, 2017)

‘Kharijism’ and ‘the Kharijites’: The Case of Early Islamic Iran - Bernheimer, Teresa (Panel 65 reconsidering Kharijism in early Islamic history, 2017)

Rebels, Zealots, Heretics? Reconsidering Kharijism in Early Islam - Hagemann, Hannah-Lena (Panel 65 reconsidering Kharijism in early Islamic history, 2017)
Keywords: Kharijisme

Ibadi Muslims in Oman and Zanzibar: The Impact of Local Context on a Translocal Tradition - Hoffman, Valerie J. (“Shifting the Meaning: Time, Space, Connectivity and its Challenges in the Western Indian Ocean, 2017)

On Board Communities: Social Groups, Motivations and On-Board Life Regulation of the Royal Fleet Against Djerba (1429-1432) - Molins, Pol Junyent (5th biennal conference 2017 Emotions, Imaginations, and Communities in the Medieval Mediterranean, 2017)
The reign of Alfons the Magnanimous (1416-1458) is an exceptional laboratory for the social study of war. Its recurrence and the different areas where the armies were mobilized are a unique setting for observation. And it is even more outstanding thanks to the vast amount of documentation preserved, which allows us to study the period in a much wider way. The aim of this paper would be to approach the human component of the medieval Catalano-aragonese armadas studying the particular case of the Royal fleet organised by King Alfons the Magnanimous in 1432 against de Tunisian island of Djerba. Often the motivation and relationship between the sea and the men who participated in such expeditions were very diverse, heterogeneous or even non-existent. The armada became somehow an exchange between social groups, sometimes forced, of different influences –economic, social, political, cultural- of different social status, communities of diverse territories and Kingdoms of the Crown of Aragon and, finally, between seafarers and landsmen.
Keywords: Invasions chrétiennes -- Djerba

La gestion des déchets sur l’île de Djerba : un processus participatif pour des perspectives durables - Laghouane, Schéhérazade (Participation citoyenne et habitante au développement social et urbain, colloque international, 2017)
Keywords: Crises environnementales -- Djerba

Geographical and Social Origin of the Crews of the Catalano-Aragonese Royal Fleet Organized against the Tunisian Island of Djerba, 1430-1432 - Molins, Pol Junyent (Cohesion and Conflict in Iberian Maritime Borders during the Late Middle Ages: Insights from Otherness, 2017)
Keywords: Invasions chrétiennes -- Djerba

Les Tunisiens juifs de Djerba - Scherschel, Frank J. (2017)
La Fondation de la Maison de Tunisie et Beit el Bennani ont le plaisir de vous inviter au vernissage de l’exposition Les Tunisiens juifs de Djerba de Frank J. Scherschel, réalisée avec le fonds Beit el Bennani. Présentation de l’exposition La vie quotidienne des juifs de Djerba, sous l’objectif du photographe américain du magazine Life Frank J. Scherschel (1907-1981). Après avoir couvert la deuxième guerre mondiale, en Europe, pour Life, Frank J. Scherschel est venu en Tunisie entre 1956 et 1957 pour photographier les événements en rapport avec l’indépendance de la Tunisie. C’est à cette occasion, qu’il a réalisé le présent reportage sur les quartiers juifs de Djerba. Présentation de Beil el Bennani Beit el Bennani est un centre de documentation sur le patrimoine tunisien situé dans La Médina de Tunis et ouvert aux étudiants et aux chercheurs. En plus d’une riche bibliothèque, ce centre dispose aussi d’un fonds photographique et archivistique, inédit pour la plupart, axé sur des sujets liés à l’histoire et au patrimoine. Le vernissage aura lieu le mercredi 6 décembre à partir de 19h30, dans le cadre d’Art-Hop-Polis, le art hopping à la Cité internationale. Maisons participantes : Suède, Suisse, Tunisie et Etats-Unis.
Keywords: Judaïsme -- Djerba